Vasico Vaginal Fistula: A Case Report and Review of Literature (KYAMC Journal, 2018)
Women of middle age having a vesicovaginal fistula (VVF) after hysterectomy represent a devastatingcondition for the surgeon as well as patient in the society. Accurate diagnosis and proper preoperative planning are essential to see a successful outcome. Herein, we report a case of simple VVF developed after abdominal hysterectomy of middle-aged woman repaired successfully and reviewed of literature for simple VVF management and described the pathophysiology of fistula development. We performed a bibliography search carried on Pubmed using keyword "Vesicovaginal Fistula.KYAMC Journal Vol. 9, No.-3, October 2018, Page 136-138